Credibility theory and filter theory in discrete and continuous time - Ramona Maier; Michael Merz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2008)
It is well known that credibility theory in discrete time is closely related to the discrete technique of Kalman filtering. In this paper we show the close relationship between credibility theory and filter theory in discrete and continuous time as well as between credibility theory in a discrete and continuous time setting.
urn:nbn:de:bsz:21-opus-36102
Keywords: 330; Schätztheorie; Zustandsraummodell; Theorie